Genomic, Transcriptomic, and Epigenomic Features Differentiate Genes That Are Relevant for Muscular Polyunsaturated Fatty Acids in the Common Carp - Zhang, Hanyuan; Xu, Peng; Jiang, Yanliang; Zhao, Zixia; Feng, Jianxin; Tai, Ruyu; Dong, Chuanju; Xu, Jian (Frontiers in Genetics, 2019)
Polyunsaturated fatty acids (PUFAs) are a set of important nutrients that mainly include arachidonic acid (ARA4), docosahexenoic acid (DHA), eicosapentaenoic acid (EPA), and α-linolenic acid (ALA). Recently, fish-derived PUFAs have been associated with cardiovascular health, fetal development, and improvement of brain functions. Studies have shown that fish muscular tissues are rich in PUFAs, which are influenced by various factors, including genetic variations, regulatory profiles, and methylation status of desaturase genes during fatty acid desaturation and elongation processes. However, the genetic mechanism and the pathways involved in fatty acid metabolism in fishes remain unclear. The overall aim of this study was to assess differences in gene expression responses among fishes with different fatty acid levels. To achieve this goal, we conducted genome-wide association analysis (GWAS) using a 250K SNP array in a population of 203 samples of common carp (Cyprinus carpio) and identified 9 SNPs and 15 genes associated with muscular PUFA content. Then, RNA-Seq and whole genome bisulfite sequencing (WGBS) of different groups with high and low EPA, DHA, ARA4, and ALA contents in muscle, liver and brain tissues were conducted, resulting in 6,750 differentially expressed genes and 5,631 genes with differentially methylated promoters. Gene ontology and KEGG pathway enrichment analyses of RNA-Seq and WGBS results identified enriched pathways for fatty acid metabolism, which included the adipocytokine signaling pathway, arachidonic acid and linoleic acid metabolism pathway, and insulin signaling pathway. Integrated analysis indicated significant correlations between gene expression and methylation status among groups with high and low PUFA contents in muscular tissues. Taken together, these multi-level results uncovered candidate genes and pathways that are associated with fatty acid metabolism and paved the way for further genomic selection and carp breeding for PUFA traits.